AMORPHOUS SILICA SOLUBILITY AND THE THERMODYNAMIC PROPERTIES OF H4SIOO4 IN THE RANGE OF 0° TO 350°C AT PSAT - Gunnarsson I.; Arnorsson S. (My University, 2000)
The solubility of amorphous silica was determined in the temperature range 8° to 310°C at 1 bar below 100°C and at Psat at higher temperatures. Our results are consistent with previous experiments between 100° and 200°C, but at higher temperatures they indicate lower solubility. Below 100°C our result are lower than the results of some researchers, but in good agreement with others. Our solubility data have been combined with previously reported data to retrieve a temperature equation describing amorphous silica solubility. Quartz solubility data have also been assessed. The solubility equations for the reaction SiO2,s + 2H2O = H4SiO^o4 are: logKam.silica=-8.476-485.24xT-1-2.268x10-6xT2+3.068xlogT logKquartz=-34.188+197.47xT-1-5.851x10-6xT2+12.245xlogT where T is in K. They are valid in the temperature range 0° to 350°C at 1 bar below 100°C and at Psat at higher temperatures. From the quartz solubility equation and the thermodynamic properties of quartz and liquid water, the standard partial molal Gibbs energy of formation and the third law entropy of H4SiO^o4 were calculated as -1,309,181 J/mole and 178.85 J/mole/K at 25°C. The difference in the standard apparent Gibbs energy of H4SiO^o4 as calculated from quartz solubility, on one hand, and amorphous silica solubility, on the other, is about the same over the temperature range 0° to 350°C indicating that the solubility temperature equations obtained for the two solids in this study are internally consistent. This indicates that the quartz solubility data of Rimstidt (1997), which were used in this study to retrieve the quartz solubility equation, are valid and also our data on ΔG^of and S° for H4SiO^o4 at 25°C and 1 bar as well as the ΔG° temperature equation presented for this species. These new Gibbs energy values for H4SiO^o4 indicate that all silicate minerals are considerably more soluble under Earth's surface conditions than generally accepted to date, or by about 0.6 log K units at 0°C per silicon atom in the unit formula.